Hip morphology and its relationship with hip strength, mobility and lower limb biomechanics: A systematic review in adults Relação da morfologia do quadril com força, mobilidade e biomecânica dos membros inferiores: Uma revisão sistemática em adultos - Ferraz A.* (2020)
© 2020, Universidade Federal de Santa Catarina. All rights reserved.–This systematic review (PROSPERO registration n.43640) aimed to summarise and determine the quality of evidence relating hip bone morphology to (i) hip strength, (ii) mobility and (iii) lower limb biomechanics during functional activities. A standardized search on MEDLINE/PubMed, Web of Science, ScienceDirect and Scopus resulted in 17 papers that met inclusion criteria: i) original investigations with a minimal sample of n=10, ii) studies on humans and iii) presence of at least one quantitative hip morphological parameter and one hip functional (i.e. strength and mobility) and/or one lower limb biomechanical parameter. Risk of bias was assessed using the Quality Assessment of Diagnostic Accuracy Studies tool with adaptations. Sixteen out of the 17 included studies showed high risk of bias. We observed that primary evidence pointed to the influence of hip morphology on hip mobility in the transverse plane. Specifically, positive correlations between femoral anteversion angle and range of internal hip rotation in physical examination were observed. Regarding biomechanical parameters, no clear evidence of association between hip morphology, and kinematic and kinetic parameters were found. Our results point to a field that is currently under explored and future studies with low risk of bias addressing these relationships are required.